2022
DOI: 10.3390/plants11070843
|View full text |Cite
|
Sign up to set email alerts
|

The Delay of Raphanus raphanistrum subsp. sativus (L.) Domin Seed Germination Induced by Coumarin Is Mediated by a Lower Ability to Sustain the Energetic Metabolism

Abstract: In the present study, the mode of action of coumarin using the germination process as a target was investigated. A dose–response curve, built using a range of concentrations from 0 to 800 µM, allowed us to identify a key concentration (400 µM) inhibiting the germination process, reducing its speed without compromising seed development. Successively, short time-course (0–48 h) experiments were carried out to evaluate the biochemical and metabolic processes involved in coumarin-induced germination delay. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Macro- and micro-elements contained in shoots portions, collected as previously described [ see Sample collection], were quantified through ICP-MS (BRUKER Aurora-M90 ICP-MS) using the protocol previously described by Araniti et al ( 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Macro- and micro-elements contained in shoots portions, collected as previously described [ see Sample collection], were quantified through ICP-MS (BRUKER Aurora-M90 ICP-MS) using the protocol previously described by Araniti et al ( 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This also indicates that coumarins prolonged dormancy in the tubers of the long dormant genotype, but induced dormancy breaking process in the tubers of the short dormant genotype. Studies have demonstrated that coumarins induced both primary and secondary seed dormancy [116][117][118]. It has been reported that coumarins induce dormancy due to their ability to antagonize gibberellins and auxin's function, while synergizing with abscisic acid (ABA) [117,119,120].…”
Section: Secondary Metabolites and Phytohormones Metabolismmentioning
confidence: 99%
“…This also indicates that coumarins prolonged dormancy in the tubers of long dormant genotype, but induced dormancy breaking process in the tubers of short dormant genotype. Studies have demonstrated that coumarins induced both primary and secondary seed dormancy [117][118][119]. It has been reported that coumarins induce dormancy due to its ability to antagonize gibberellins and auxin's function, while synergizing with abscisic acid (ABA) [118,120,121].…”
Section: Secondary Metabolites and Phytohormones Metabolismmentioning
confidence: 99%